2020
DOI: 10.1002/jmv.26052
|View full text |Cite
|
Sign up to set email alerts
|

Effects of methylprednisolone use on viral genomic nucleic acid negative conversion and CT imaging lesion absorption in COVID‐19 patients under 50 years old

Abstract: The use of corticosteroids has been controversial in viral pneumonia. In most cases, application of methylprednisolone in severe and critical viral pneumonia patients can quickly alleviate the symptoms of dyspnea and prevent disease progression. However, some scholars have confirmed that corticosteroids delayed the body's clearance of the virus. In our retrospective non-randomized study, 34 patients under 50 years old and diagnosed with coronavirus disease 2019 (COVID-19) were included. According to the given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 18 publications
0
31
0
1
Order By: Relevance
“…The indication for corticosteroids was reported in 7/22 studies and varied: most frequently it comprised (a combination of) worsening oxygenation, severe radiological ndings, ICU admission, or persistence of in ammatory symptoms. [33,[38][39][40][41][42][43] The median time of initiation after admission was reported in 8/22 studies and varied from 24 hours after hospital admission, [44] immediately after ICU admission [43] to approximately eight to fourteen days after onset of symptoms. [23,41,42,[45][46][47] One study compared early (average 2 days after hospital admission) to late corticosteroid administration (average 5 days after hospital admission).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The indication for corticosteroids was reported in 7/22 studies and varied: most frequently it comprised (a combination of) worsening oxygenation, severe radiological ndings, ICU admission, or persistence of in ammatory symptoms. [33,[38][39][40][41][42][43] The median time of initiation after admission was reported in 8/22 studies and varied from 24 hours after hospital admission, [44] immediately after ICU admission [43] to approximately eight to fourteen days after onset of symptoms. [23,41,42,[45][46][47] One study compared early (average 2 days after hospital admission) to late corticosteroid administration (average 5 days after hospital admission).…”
Section: Resultsmentioning
confidence: 99%
“…[33] Methylprednisolone was the most frequently used corticosteroid (13/22 studies). [33,[37][38][39][40][42][43][44]46,[48][49][50][51] In two studies methylprednisolone, hydrocortisone, or dexamethasone was used. [36,41] Ling et al used prednisolone or dexamethasone, [52] and Horby et al reported on dexamethasone use.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations